The Improvement of Reading Skills Through Pictorial Word Cards in Second Grade Students of SDN 36 Sungai Ambawang - Suharlan Suharlan (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2019)
Based on the fact that teachers feel the low reading skills of students because they feel bored and lack of interest in learning. It is because the teacher does not use media that made students interesting and used the method of spelling and is not supported by supporting books such as pictorial storybooks that make students interested in reading. For this reason, the teacher used pictorial word cards to improve students reading skills. The form of research is classroom action research, collaborative in nature, the subjects in this study were students of second-grade SDN (State Elementary School) 36 Sungai Ambawang, and researchers who also acted as teachers. The procedure in this study follows the main stages, namely planning, implementation, observation, and reflection. Research techniques are direct observation and measurement techniques, data collection tools used are observation sheets and tests. The results of the implementation of the act of learning to read using pictorial cards in each cycle always increases. In the first cycle, the success of students' reading skills achieved 55.55%, then in the second cycle increased to 100%. With an average value of 62.22 in the first cycle and the second cycle, the average value increased to 77.77. Based on the description above, it can generally be concluded that the use of pictorial word cards can improve the reading skills of grade 1 students of SDN 36 Sungai Ambawang. Thus the pictorial word card media can be used during the learning process of reading to improve students' reading skills.